2002
DOI: 10.1080/10915810290096315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Reproductive Toxicity and Embryotoxicity of Insulin Glargine (LANTUS) in Rats and Rabbits

Abstract: Insulin glargine (LANTUS) is a new insulin analog that has a prolonged duration of action with no pronounced peak of activity, rendering it an ideal basal insulin for the treatment of diabetes. The aim of these studies was to assess the reproductive and embryotoxicity of insulin glargine. Reproductive toxicity was assessed in 25 male and 25 female Wistar rats per group treated with a daily subcutaneous injection of control; 1 IU/kg, 3 IU/kg, and 10 IU/kg insulin glargine; or 3 IU/kg NPH insulin in the prematin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…On the 21 st day of the study a caesarean section is performed and felaser with haemorrhagic bullae, limb malformations, exencephally, cleft palates, open eyelids, detail deformities, mortality and the number of live and dead animals are noted. Embryo toxicity assays such as embryonic stems cell test, micromass embryotoxicity assay and whole rat embryotoxicity assays can be done (Kimm-Brinson & Ramsdell, 2001;Hofmann et al, 2002;Booth et al, 2010). During generation reproduction toxicity study, genetic toxicity testing can be carried out to identify gene mutations, chromosomal changes and alterations on the DNA sequency.…”
Section: Two Generation Reproduction Toxicity Studiesmentioning
confidence: 99%
“…On the 21 st day of the study a caesarean section is performed and felaser with haemorrhagic bullae, limb malformations, exencephally, cleft palates, open eyelids, detail deformities, mortality and the number of live and dead animals are noted. Embryo toxicity assays such as embryonic stems cell test, micromass embryotoxicity assay and whole rat embryotoxicity assays can be done (Kimm-Brinson & Ramsdell, 2001;Hofmann et al, 2002;Booth et al, 2010). During generation reproduction toxicity study, genetic toxicity testing can be carried out to identify gene mutations, chromosomal changes and alterations on the DNA sequency.…”
Section: Two Generation Reproduction Toxicity Studiesmentioning
confidence: 99%
“…90 No data are available as yet on the capacity of these insulin analogues to cross the placenta. In a case-control pilot study involving 22 GDM cases treated with insulin glargine, Price et al could find no differences in maternal and fetal outcomes.…”
Section: Duration and Frequencymentioning
confidence: 99%
“…In animal studies, no embryotoxic effects have been demonstrated. 57 It does have theoretical risks in pregnancy because of its known activation of insulin-like growth factor 1 (IGF-1) receptors and mitogenic potency, however, small cohort studies have not demonstrated any concerns. 58 For women well-controlled on glargine prior to pregnancy it may be difficult to return to intermediate-acting insulins.…”
Section: Achieving Glycaemic Control In Women With T2dmmentioning
confidence: 99%